IMPACT OF DAIRY SUPPORT SERVICES AND STRATEGIES ON REDUCTION OF COST OF MILK PRODUCTION IN DIFFERENT DAIRY PRODUCTION SYSTEMS IN BANGLADESH: IMPLICATIONS FOR RURAL LIVELIHOOD IMPROVEMENT - Uddin, M.M.; Hemme, T.; Ndambi, O.A.; Khan, M.J. (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
The objective of this study was to analyse the impact of set of dairy supporting policies within the framework of the government âNational Livestock Development Policy (NLDP)â on the potential for reduction of cost of milk production in small-scale dairy farmers under different production systems. This study further aims at identifying the link among increasing household income and rural livelihoods-thus reducing poverty. This study applies the method developed by the International Farm Comparison Network (IFCN). The underlying principle of this method is the application of the concept of âTypical Farm Approach (TFA)â and Technology Impact Policy Impact Calculations (TIPI-CAL) model. Three typical farms from three production systems (e.g. extensive, intensive and traditional) were selected from three agro-ecological zones. The required data collection was done in two steps: first, the data were collected from three baseline typical farms (status quo) operating without policy by applying the âPanel Approachâ. In the second step, 10 different dairy supporting policy scenarios and technologies were simulated and applied in each of the base line farms in each production system and data were collected from 30 farms using the base farm as the status quo farm. The data were analysed by utilizing the extended version of TIPI-CAL (Technology Impact Policy Impact Calculations) model (TIPI-CAL software version 5.1). The results showed that improved dairy support services: improved veterinary services (IM-VHS), improved marketing access (IM-MKS), improved feeding and nutritional services (IM-FNS), community based fodder production system (CB-FPS), national breeding programme (NL-BRP) showed the highest impact on increasing milk productivity, decreasing milk production cost, increasing income from dairy and overall household income in all three production systems compared with base line farms. However, the magnitude of the impacts substantially differs among the production systems. This study also reveals that that there is a direct link among increasing income and reducing poverty since the household income increases as a result of implementing dairy support services to a level above the poverty line (1.9 US$/day equivalent to 147.96 BDT). This study results could be useful for prioritizing the policies on delivery of support services and technology and are expected to be helpful as a benchmark to implement the âdraft policy proposalâ by the Ministry of Fisheries and Livestock (MOFL) in Bangladesh.